Gender differences on oxidative stress markers and complement component C3 plasma values after an oral unsaturated fat load test - Ferri, Jordi; Navarro, Inmaculada; Alabadí, Blanca; Bosch-Sierra, Neus; Benito, Esther; Civera, Miguel; Ascaso, Juan F.; Martinez-Hervas, Sergio; Real, Jose T. (Clínica e investigación en arteriosclerosis (Internet, English ed.), 2020)
Post-prandial lipaemia (PL), oxidative stress (OS), and complement component C3 (C3) values are related to the atherosclerosis process. The post-prandial response of C3 after an oral fat load test (OFLT) using unsaturated fat is poorly addressed. The aim of this study was to analyze and compare the post-prandial response of OS markers and C3 values in men and women after an OFLT using unsaturated fat. The study included a total of 22 healthy subjects with normal lipids and normal blood glucose (11 men and 11 pre-menopausal women). An oral unsaturated fat load test (OFLT: 50g fat per m2 body surface) was performed using a commercial liquid preparation of long chain triglycerides (Supracal®). OS markers and C3 were measured using standardized methods at fasting state and every 2h up to 8h after the OFLT. Men showed statistically significant higher C3, oxidized glutathione (GSSG), and oxidized-reduced glutathione (GSSG/GSH) ratio values at fasting state compared to that obtained in women. In addition, post-prandial C3 values and GSSG/GSH ratios were significantly higher in men compared to women. The GSSG value and GSSG/GSH ratio significantly decreased in men after the OFLT compared to fasting values. In contrast, the post-prandial OS markers decrease observed in women was not statistically significant. In fasting state, men showed higher statistically significant C3 values and OS markers than women. The post-prandial OS markers (GSSG and GSSG/GSH ratio) significantly decrease after the OFLT with unsaturated fat in men compared to women. Los valores de lipemia postprandial (PL), estrés oxidativo (OS) y componente C3 del complemento (C3) están relacionados con el proceso de aterosclerosis. La respuesta postprandial de C3 tras una sobrecarga oral de grasa (OFLT) utilizando grasa insaturada no es completamente conocida. Nuestro objetivo fue analizar y comparar la respuesta postprandial de los marcadores de OS y los valores de C3 en hombres y mujeres después de una OFLT utilizando grasa insaturada. Estudiamos 22 sujetos normolipidémicos y normoglicémicos (11 hombres y 11 mujeres premenopáusicas). Se realizó una sobrecarga oral con grasa insaturada (OFLT: 50g de grasa por m2 de superficie corporal) utilizando una preparación líquida comercial de triglicéridos de cadena larga (Supracal®). Los marcadores OS y C3 se midieron utilizando métodos estandarizados en estado de ayuno y cada 2 horas hasta 8 horas después de OFLT. Los hombres mostraron valores significativamente mayores de C3, glutatión oxidado (GSSG) y glutatión reducido (GSSG/GSH) en estado de ayuno en comparación con los obtenidos en mujeres. Además, los valores de C3 postprandiales y la relación GSSG/GSH fueron significativamente más altos en los hombres que en las mujeres. El valor GSSG y la relación GSSG/GSH disminuyeron significativamente en los hombres después de OFLT en comparación con los valores de ayuno. En contraste, la disminución de marcadores postprandiales de OS observada en mujeres no fue estadísticamente significativa. En ayunas, los hombres muestran valores estadísticamente mayores de C3 y marcadores OS que las mujeres. Los marcadores OS postprandial (GSSG y GSSG/GSH ratio) disminuyen significativamente tras OFLT con grasa insaturada en los hombres en comparación con las mujeres.